2010
DOI: 10.4067/s0717-95022010000100029
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Polymorphism and Morphometrical Correlates in the West African Dwarf Sheep of Nigeria

Abstract: Red cells extracted from blood samples taken by jugular venipuncture from a total of thirty-six traditionally managed adult West African Dwarf rams and ewes were subjected to starch gel electrophoresis, stained to reveal the activities of different allelemorphs at hemoglobin locus and analyzed. The studies was aimed at examining genetic variation as well as pattern of segregation at the locus and unveil possible association that might exist between the phenotypes and selected zoometrical traits. From the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
3
4
2
Order By: Relevance
“…The haemoglobin genotypes, two homozygotes AA and BB and one heterozygote AB, detected in this study agree with the general observation that alleles A and B at the same locus are capable of producing three different genotypes AA, AB and BB, in different species of animals (Zaragoza et al, 1987;Tunon et al, 1989). The finding also agrees with Rodero et al (1996) in Lebrijan Churro breed of Andalusia sheep but not in Merino sheep and Akinyemi and Salako (2010) in WAD sheep. The proportions of the haemoglobin genotypes at 52% HbAA, 22% HbAB and 27% HbBB in this study differ from the 100% HbAA reported by Dafur et al (2019) in WAD sheep; the 72% HbAA and 28% HbAB obtained by Osaiyuwu and Salako (2018) in WAD sheep; the 88.89% HbAA and 11.11% HbAB in WAD sheep obtained by Akinyemi and Salako (2010); the 0.00% HbAA, 11.11% HbAB and 88.89% HbBB in Lebrijan Churro breed of Andalusia sheep and the 17% HbAA, 20.65% HbAB and 77.17% HbBB for the Grazalema Merino sheep reported by Rodero et al (1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The haemoglobin genotypes, two homozygotes AA and BB and one heterozygote AB, detected in this study agree with the general observation that alleles A and B at the same locus are capable of producing three different genotypes AA, AB and BB, in different species of animals (Zaragoza et al, 1987;Tunon et al, 1989). The finding also agrees with Rodero et al (1996) in Lebrijan Churro breed of Andalusia sheep but not in Merino sheep and Akinyemi and Salako (2010) in WAD sheep. The proportions of the haemoglobin genotypes at 52% HbAA, 22% HbAB and 27% HbBB in this study differ from the 100% HbAA reported by Dafur et al (2019) in WAD sheep; the 72% HbAA and 28% HbAB obtained by Osaiyuwu and Salako (2018) in WAD sheep; the 88.89% HbAA and 11.11% HbAB in WAD sheep obtained by Akinyemi and Salako (2010); the 0.00% HbAA, 11.11% HbAB and 88.89% HbBB in Lebrijan Churro breed of Andalusia sheep and the 17% HbAA, 20.65% HbAB and 77.17% HbBB for the Grazalema Merino sheep reported by Rodero et al (1996).…”
Section: Discussionsupporting
confidence: 91%
“…Data were collected on Mendelian traits such as the horn status, wattle status and hair length on sex basis as described by Akinyemi and Salako (2010). Blood samples were collected from the adult sheep of both sexes by jugular venipuncture into well labeled Bijou bottles containing a speck of ethylenediaminetetraacetic acid (EDTA) as anticoagulant.…”
Section: Data Collection and Laboratory Analysismentioning
confidence: 99%
“…In the present study, Hb type only influenced packed cell volume (PCV) and haemoglobin concentration, animals with HbAA recorded higher values of PCV than animals with HbAB and HbBB. Carriers of haemoglobin AA genotype have been reported to have better functional properties such as affinity for oxygen, higher haemoglobin concentration and packed cell volume (FAO, 2008;Akinyemi and Salako, 2010) The effect of potassium types significantly influenced Na concentration. It had been observed that HK animals had less concentration of Na than LK (Galip and Elmaci, 2001).…”
Section: Effect Of Haemoglobin and Potassium Polymorphism On Blood Prmentioning
confidence: 99%
“…), are trypanotolerant (Geerts et al . ), have rapid growth (Sowande and Sobola ) and are rich in genetic variation (Akinyemi and Salako ). Many African farmers use tree‐based browse as feed supplements, as these feed sources require no cultivation.…”
Section: Introductionmentioning
confidence: 99%